Leprosy and tuberculosis concomitant infection: A poorly understood, age-old relationship - Rawson, Timothy Miles; Anjum, Vaseem; Hodgson, Jasmin; Rao, A Kameswara; Murthy, Krishna; Rao, Pss Sundar; Subbanna, Jonnalagada; Rao, PV Ranganadha (Leprosy review, 2014)
Historically, archaeological evidence, post-mortem findings and retrospective analysis of leprosy institutions' data demonstrates a high observed incidence of concomitant infection with leprosy and tuberculosis (TB). However, reports of concomitant infection in the modern literature remain scarce, with estimates of annual new case detection rates of concomitant infection at approximately 0.02 cases per 100,000 population. Whilst the mechanism for this apparent decline in concomitant infections remains unclear, further research on this topic has remained relatively neglected. Modelling of the interaction of the two organisms has suggested that the apparent decline in observations of concomitant infection may be due to the protective effects of cross immunity, whilst more recently others have questioned whether it is a more harmful relationship, predisposing towards increased host mortality. We review recent evidence, comparing it to previously held understanding on the epidemiological relationship and our own experience of concomitant infection. From this discussion, we highlight several under-investigated areas, which may lead to improvements in the future delivery of leprosy management and services, as well as enhance understanding in other fields of infection management. These include, a) highlighting the need for greater understanding of host immunogenetics involved in concomitant infection, b) whether prolonged courses of high dose steroids pre-dispose to TB infection? and, c) whether there is a risk of rifampicin resistance developing in leprosy patients treated in the face of undiagnosed TB and other infections? Longitudinal work is still required to characterise these temporal relationships further and add to the current paucity of literature on this subject matter.